Educational Values in Lubuk Larangan Local Wisdom in Rantau Pandan Village, Bungo Regency, Jambi Province - Bahar, Mahdi; Wahyuni, Anny; Adi Saputra, Muhammad (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research explores the educational values embedded in the local wisdom of Lubuk Larangan in Rantau Pandan Village, Bungo District. To achieve this goal, the method used is qualitative research with a descriptive-analytical approach. Data was collected through interviews, observations, and documentation, and data validity was maintained through data source triangulation. The results of this research reveal that the local wisdom of Lubuk Larangan encompasses several valuable educational values. First, there are moral and ethical education values that promote awareness of good and proper behavior. Second, social education values help strengthen interpersonal relationships in the community and promote cooperation. Third, religious education values inspire spiritual and moral beliefs among the local population. Lubuk Larangan serves as an important public space for education for the people of Rantau Pandan. Through the introduction and understanding of these values, the community can preserve and pass on their cultural heritage while enhancing their understanding of ethics, morals, and deep-seated social and religious values. The results of this research make a significant contribution to appreciating and utilizing local cultural richness as a source of valuable educational values.